Space management : GIS web-based UiTM Perlis / Said Ramadhan Dol Hamid - Dol Hamid, Said Ramadhan (2020)
Interactive campus mapping which can be accessed using web browser is needed to each campus university because it can help user to explore campus university with easily and help any users does not understand about plan campus university to be known about plan campus university. This research was conducted at Universiti Teknologi MARA (UiTM) Perlis Branch. This project aim to provide an online platform to view the UiTM Perlis building space management. To achieve the aim, several objective includes which is i) to prepare the spatial and database of UiTM Perlis building space management, ii) to display space of UiTM Perlis through ArcGIS Online and iii) to test the web-based among students. This study used the ArcGIS Desktop and ArcGIS Online to prepare the database of UiTM Perlis with data provided in hard copy base map and also ground data collection. The database was published in the ArcGIS Online and make the system application as interactive map through the Web AppBuilder. This application was tested to the four group categories such as student, staff, alumni and public. From the testing, the user will answer questionnaire to conclude analysis for this project. Therefore, this study contributed to improvement of current mapping medium that has been using in UiTM Perlis for a long time from using hardcopy mapping to online platform mapping. It also prove that UiTM Perlis Branch is keep up to date with the current state of IT technology.